Bosnia and Herzegovina : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
Bosnia and Herzegovina has come a long way, but has to achieve more in terms of economic transition. The core and most urgent economic task is corporate restructuring. Labor market institutions need to be transformed alongside. The fiscal and structural reform agenda will require strengthened fiscal institutions and macroeconomic data. The financial policies have been well calibrated. The agenda will tax implementation and absorptive capacity to its limits. The strength of the government's commitment to confront the structural challenges ahead will be decisive.